The manifestation of the Younger Dryas event in the East Asian summer monsoon margin: New evidence from carbonate geochemistry of the Dali Lake sediments in northern China. (July 2018) - Fan, Jiawei; Xiao, Jule; Wen, Ruilin; Zhang, Shengrui; Wang, Xu; Cui, Linlin; Liu, Yanhong; Li, He; Yue, Jiaojiao
The processes and mechanisms of the Younger Dryas (YD) event in the modern northern margin of the East Asian summer monsoon (EASM) are still heatedly debated. This study presents new high-resolution ( 25 years) records of elements and stable isotopes of <38-µm calcites from a sediment core from Dali Lake in order to investigate the climatic change in the EASM margin at the last glacial–interglacial transition. The <38-µm calcites in the Dali Lake sediments are cubical or rhombohedral, implying that they are predominated by endogenic calcites precipitated within the water body of the lake. High values of Ca and Mg concentrations of the endogenic calcites are interpreted as strong evaporation and low dissolved CO2 concentration of the lake water related to high regional temperature. Concurrent increases in δ 13 C and δ 18 O values of the endogenic calcites are interpreted as the result of intensified evaporation associated with high temperature or low precipitation in the region. These data indicate that the climate in the Dali Lake region was relatively warm and wet from 15, 500 to 12, 800 and from 11, 550 to 10, 000 cal. yr BP, and cold and dry from 12, 800 to 11, 550 cal. yr BP, which was generally supported by the evidence from the data of sedimentary organic matter from the same sediment core. In addition, the abruptness of the temperature change in the Dali Lake region from 12, 800 to 11, 550 cal. yr BP could be corresponded, within age uncertainties, to the YD cold reversal occurring over northern high latitudes. The atmospheric coupling between the North Atlantic region and the EASM margin was proposed as the dominant pattern influencing the climatic change in the Dali Lake region during the YD event.